1999
DOI: 10.1029/1999gl010434
|View full text |Cite
|
Sign up to set email alerts
|

Unusual ocean‐atmosphere conditions in the tropical Indian Ocean during 1994

Abstract: Abstract. The southeastern tropical Indian Ocean (SE-TIO) was characterized by unusually cold sea surface temperature (SST) and strong northwestward alongshore surface winds during 1994. Using multi-source data sets including ocean model simulation, two key processes are identified for the SETIO cooling. Entrainment cooling produced most of the negative SST anomaly near the coast whereas evaporative cooling dominated the process away from the coast. Convection was anomalously suppressed over SETIO and the dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
216
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(232 citation statements)
references
References 13 publications
16
216
0
Order By: Relevance
“…The convection in the eastern Indian Ocean is suppressed during the positive IOD events, whereas the convection in the central and western Indian Ocean is enhanced. Behera et al (1999) have shown that the coupling between the SST cooling and the suppressed convection in the eastern Indian Ocean gave rise to further easterly wind anomalies during the typical IOD event of 1994. Using a simple Matsuno-Gill type model, Saji and Yamagata (2001) have also shown that the atmospheric linear response to such changes in the heat source of the eastern Indian Ocean strengthens the easterly wind anomalies, which in turn are responsible for the evolution of the SST dipole.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The convection in the eastern Indian Ocean is suppressed during the positive IOD events, whereas the convection in the central and western Indian Ocean is enhanced. Behera et al (1999) have shown that the coupling between the SST cooling and the suppressed convection in the eastern Indian Ocean gave rise to further easterly wind anomalies during the typical IOD event of 1994. Using a simple Matsuno-Gill type model, Saji and Yamagata (2001) have also shown that the atmospheric linear response to such changes in the heat source of the eastern Indian Ocean strengthens the easterly wind anomalies, which in turn are responsible for the evolution of the SST dipole.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the wind is even more significant at the thermocline depths through the oceanic adjustment process ; the thermocline rises in the east and deepens in the central and western parts. Since the seasonal southeasterly winds along the Sumatra coast are also strengthened during the positive IOD events, the induced coastal upwelling causes strong SST cooling in the east (Behera et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 1a-1e demonstrate that, the IOD SSTA pattern indeed exists during JJAS season of aforementioned dipole years, and the Boxes A and B reasonably represent the two different poles of the IOD. Study of some recent dipole events suggests that IOD is an air-sea interaction phenomenon (Behera et al 1999;Webster et al 1999). When the IODMI is positive, it may lead to droughts over the Indonesian region, while simultaneously causing heavy rains and floods over East Africa.…”
Section: Introductionmentioning
confidence: 99%
“…During the 1990s, the well-established link between El Niño and the Indian monsoon failed. In 1994, the southeast tropical Indian Ocean experienced unusually cold SSTs and southeasterly winds (Behera et al, 1999 Figure 9. Schematic of the Atlantic coupled mode and its feedbacks, showing the warm phase leading to a succeeding cold phase a combination of enhanced upwelling along the eastern shore of the Indian Ocean with evaporative cooling offshore, atmosphere convection was suppressed in the region.…”
Section: Tropical Air-sea Coupling In the Atlantic And Indian Oceansmentioning
confidence: 99%